POTENSI TAPE SEBAGAI PANGANAN TRADISIONAL TERHADAP EFEK HEPATOTOKSIK TIKUS TERINDUKSI KARBON-TETRAKLORIDA - Gidion Krisnadi Yoseph; Christiana Destia Anggraeni; Ni Luh Putu Dian Prawita Putri; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: The purpose of this study was to determine the effect of Tape that has an alcoholiccompound, to the hepatotoxic effect in the rat induced Carbon Tetrachloride. And also determinewhich fermentation time of the Tape can give effect to the hepatotoxic in the rat induced Carbontetrachloride. Healthy rats were randomly divided into 7 groups of 5 animals in each. Group 1received carbon tetrachloride 2ml/kgBW treated intraperitoneal. Group 2-4 were given Tapesuspension 18g/kgBW once daily for 6 days with different fermentation time (3, 5, 7 days). Group5-7 were given Tape suspension 18g/KgBW once daily for 6 days with different fermentationtime and carbon tetrachloride was given on the 7th day. Blood sample from all groups wasobtained by sinus orbitalis after 24 hours application for estimation the serum level oftransaminase. The result showed that Tape suspension had a potential effect to reduce thehepatotoxicity induced by carbon tetrachloride. Tape suspension with 5 days fermentationwas significantly decreased serum level of transaminase (P0,05) upon carbon tetrachlorideinduced hepatic damage in rats.Keywords: hepatotoxicity, tape, fermentation time,carbon tetrachloride